The Woman Who Ran For President: The Many Lives of Victoria Woodhull - Underhill, Lois Beachy (Bridgeworks, 1995)
Victoria Woodhull was a feminist pioneer who rose up from poverty to become the first woman Wall Street broker, the first woman to testify before Congress and the first woman to run for president. A beautiful woman and a spellbinding public speaker, she was also a figure of scandal--a divorcee and practicing clairvoyant turned muckracking newspaper publisher, a free-love advocate (and practitioner), and a socialist.